1997
DOI: 10.1159/000185356
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low-Dose Oral and Intravenous Dexamethasone Administration on Growth Hormone Secretion in Children

Abstract: Acute dexamethasone administration (2 mg/m2 i.v. and 4 mg orally) increases growth hormone (GH) release in children. We evaluated the effect of a low intravenous dose (1 mg/m2) of dexamethasone on GH secretion in 8 short normal children and in 6 GH-deficient children. There was a significant GH increase at 120, 150 and 180min in short normal children (maximal value: 18.9 ± 2.1 μg/l; X ± EP), compared to placebo administration. In contrast, no significant GH elevation was seen in GH-defici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 23 publications
(41 reference statements)
1
3
0
1
Order By: Relevance
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The positive e ect of the exogenous corticosterone on the secretion of GH reported here accords with data from a number of clinical studies which have demonstrated prompt increases in serum GH following acute administration of glucocorticoids by mouth or parenterally (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998) and advocated a role for GCs in the diagnosis of GH de®ciency (Pineda et al, 1994;Pellini et al, 1998). Our ®nding that the hypersecretion of GH provoked by a single injection of corticosterone in the rat is (a) blocked speci®cally by central but not peripheral administration of anti-annexin 1 pAb and (b) mimicked by a central injection of annexin 1 Ac2 ± 26 suggests that the steroid exerts its positive in¯uence on the GH axis via an annexin 1-dependent mechanism within the hypothalamus.…”
Section: Discussionsupporting
confidence: 88%
“…This is due largely to actions of the steroids at the hypothalamic level which increase the expression and release of somatostatin (Papachristou et al, 1994;Fife et al, 1996;Lam & Srivastava, 1997) and decrease the production of GH releasing hormone (GHRH, Fernandez-Vazquez et al, 1995;Fife et al, 1996;Lam & Srivastava, 1997). Paradoxically, the impact of the consequent change in the hypothalamic drive to the somatotrophs is attenuated by concomitant actions of the steroids at the pituitary level which increase GHRH receptor (Tamaki et al, 1996;Miller & Mayo, 1997) and GH (Oosterom et al, 1983;Evans et al, 1992;Nogami et al,complicated by ®ndings in man that acute administration of GCs causes a transient (3 ± 4 h), but marked, increase in serum GH (Buguera et al, 1990;Casanueva et al, 1990;Muruais et al, 1991;Pineda et al, 1994;Pinto et al, 1997;Pellini et al, 1998). The mechanism by which the GCs evoke this secretory response is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A resposta à dexametasona foi tão potente quanto à obtida com clonidina e com exercício+propranolol, sendo maior do que observada após hipoglicemia e menor do que após GHRH. Dados por nós obtidos demonstraram que a administração endovenosa de doses menores de dexametasona (1mg/m 2 de superfície corpórea) ou a utilização deste esteróide por via oral (2mg) também promove um aumento acentuado dos níveis de GH em crianças normais (41). Como não existem efeitos colaterais, este estímulo pode ser utilizado como teste diagnóstico de reserva de GH.…”
Section: Hipercortisolismo Agudounclassified
“…Acute glucocorticoid administration increases GH secretion (Casanueva et al, 1988Burguera et al, 1990;Miell et al, 1994;Thakore & Dinan, 1995;Pinto et al, 1997;Pellini et al, 1998). Maximal GH stimulatory effect is usually seen 3-4 h after both iv and oral dexamethasone administration, but GH values can remain elevated during the following 60-120 min (Casanueva et al, 1988Burguera et al, 1990).…”
mentioning
confidence: 99%
“…The mechanisms involved in the GH stimulatory effect of glucocorticoids remain unclear. It has been suggested that these steroids decrease hypothalamic somatostatin release, but a direct pituitary action should also be considered (Bridson & Kohler, 1970;Martial et al, 1977;Vale et al, 1983 Dieguez et al, 1992;Popovic et al, 1993;Pinto et al, 1997).…”
mentioning
confidence: 99%